The Formation, Value and Realization of Xi Jinping's Thought on Building a Community with a Shared Future for Mankind - Guo Hailong; Wang Xi (Contemporary Social Sciences, 2017)
A community with a shared future for mankind refers to equal, all-win, safe and inclusive human collective organizations between countries. Xi Jinping’s thought on building a community with a shared future for mankind is deeply rooted in the excellent traditional Chinese culture, and is the “Chinese diagnosis” made, and “Chinese plans” proposed, for world problems. It provides the realistic possibility to advocate for and construct a community with a shared future for mankind for development, peace and security of the world and global governance. We should adhere to the principles of step-bystep implementation, equality and mutual assistance, respect for differences, eco-friendly development and inclusiveness, to achieve a community with a shared future for mankind